Impact of Community Mass Treatment with Azithromycin for Trachoma Elimination on the Prevalence of Yaws. - Michael Marks; Ventis Vahi; Oliver Sokana; Kai-Hua Chi; Elliot Puiahi; Georgina Kilua; Allan Pillay; Tenneth Dalipanda; Christian Bottomley; Anthony W Solomon; David C Mabey (Public Library of Science (PLoS), 2015)
BACKGROUND:Community mass treatment with 30 mg/kg azithromycin is central to the new WHO strategy for eradicating yaws. Both yaws and trachoma--which is earmarked for elimination by 2020 using a strategy that includes mass treatment with 20 mg/kg azithromycin--are endemic in the Pacific, raising the possibility of an integrated approach to disease control. Community mass treatment with azithromycin for trachoma elimination was conducted in the Solomon Islands in 2014. METHODS:We conducted a study to assess the impact of mass treatment with 20 mg/kg azithromycin on yaws. We examined children aged 5-14 years and took blood and lesion samples for yaws diagnosis. RESULTS:We recruited 897 children, 6 months after mass treatment. There were no cases of active yaws. Serological evidence of current infection was found in 3.6% (95% CI= 2.5-5.0%). This differed significantly between individuals who had and had not received azithromycin (2.8% vs 6.5%, p=0.015); the prevalence of positive serology in 5-14 year-olds had been 21.7% (95% CI=14.6%-30.9%) 6 months prior to mass treatment. Not receiving azithromycin was associated with an odds of 3.9 for infection (p=0.001). National figures showed a 57% reduction in reported cases of yaws following mass treatment. DISCUSSION:Following a single round of treatment we did not identify any cases of active yaws in a previously endemic population. We found a significant reduction in latent infection. Our data support expansion of the WHO eradication strategy and suggest an integrated approach to the control of yaws and trachoma in the Pacific may be viable.